Resistência impertinente : a subversão do Regime no humor de Ziraldo - Besagio, Natália Martins (2017)
This research analyzes the conditioning of Brazilian political imaginary and public opinion on Brazil-US relations during the second Vargas Administration. The study aims to enable the survey of the stereotypes forged and conveyed in order to legitimate the friendly and hostile sets that outlined the relations between both countries in this period. Therefore, we went about this task by performing the investigation of the publications of Última Hora, an influent newspaper of national circulation from Rio de Janeiro which represented the interests of Vargas? government. Confronting the editions published between June 1951, when the paper was first printed, and august 1954, when Vargas committed suicide, with complementary sources, we analyzed which sets of meanings and mental images were shared and spread in order to make the Vargas? ?nationalist bargain? legitimate among Brazilian society. In other words, we investigated the strategies used by the political circles that supported the government to ?manufacture consent? among the public opinion in order to form or reinforce stereotypes about Brazil-US relations